องค์ประกอบทางการออกแบบแสงประดิษฐ์บนยอดอาคารสูงในกรุงเทพมหานคร - วิศวกร ทางทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The present research studied the patterns of lighting design of Bangkok skyscrapers during 1970-2010. This study was conducted to gather useful information for the future design of skyscrapers. The research examined the elements associated with the design, specifically the styles of architecture and their current lighting configuration. Thirty skyscrapers in Bangkok were selected as case studies. Data collection was conducted through the interviews of architects and the survey of actual sites. Data collection and data analysis suggested that there were 12 basic lighting designs for skyscrapers; for example, a design which highlighted the outline or the structure of the building. It was also found that some of the lighting designs could be adapted to suit any architectural plan. Additionally, an analysis of building design based on fundamental theories suggested that there were five main types of design among the 30 case studies; for example, a design which was derived from elaboration of building structure or from simplification of form only. In this sense, certain types of lighting designs found in this study may only be appropriate for specific types of building. Derived from the analysis of architectural designs and their lighting, the researcher exemplified each of building types from the five main groups and proposed the options for each building. Taking into consideration the building shape, the researcher used Photoshop to create different choices of possible lighting designs for each building. These selections were gathered from those of the case studies so as to show the design possibilities. This research presented the possible lighting designs for skyscrapers based on those presently available. Architects or anyone who is interested in lighting design can therefore apply the findings from this study to other future designs.